College students' attitudes on the causes of infidelity - Koss, Jamie; Lee, Kaisa L. (University of Wisconsin--Stout. Research Services, 2007)
Infidelity is a problem in today’s society associated with instability in relationships and the high divorce rates. The study consisted of 23 male and female students at a Midwestern university. It was hypothesized that males would perceive sexual attraction as a primary cause of infidelity while females would perceive relationship dissatisfaction as a primary cause. Survey data was statistically analyzed using frequencies, cross-tabulations and a reliability analysis. Findings supported the literature and hypothesis in that more males viewed sexual attraction as a primary cause of infidelity and more females viewed relationship dissatisfaction as a primary cause. It is important for practitioners to be aware of the problems infidelity causes in relationships and further researchers could investigate root causes for preventative and proactive actions.
Research article with tables.
Keywords: committed relationships; relationship dissatisfaction; infidelity; Sexual attraction; College students--Sexual behavior; Sexual ethics; Man-woman relationships